2001
DOI: 10.1177/000331970105200803
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Circumflex Coronary Artery: Benign or Predisposed to Selective Atherosclerosis

Abstract: Anomalous origin of the circumflex coronary artery from the right sinus of Valsalva is the most common coronary anomaly and is usually considered benign. Although several researchers in the past believed that aberrancy predisposes this vessel to accelerated atherosclerosis, this could not get wide acceptance owing to lack of convincing data. To examine the suggestion that atherosclerosis affects the anomalous circumflex artery more severely, the authors reviewed the clinical and angiographic features of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 15 publications
3
51
1
1
Order By: Relevance
“…Samarendra et al (2001) affirm that the circumflex branch of the coronary artery originated in the right side, is the most common "benign" coronary anomaly and is not considered the cause of ischemia or myocardial infarction, which confirm the conclusions of Click et al (1989), when they claim that the most common anomaly involving the coronary artery is the one of the circumflex branch, although such anomalies are not common in adults. It must be considered however, that this condition can be present at birth, being little symptomatic during childhood, and being found incidentally through the coronary arteriography or necropsy.…”
Section: Discussionsupporting
confidence: 67%
“…Samarendra et al (2001) affirm that the circumflex branch of the coronary artery originated in the right side, is the most common "benign" coronary anomaly and is not considered the cause of ischemia or myocardial infarction, which confirm the conclusions of Click et al (1989), when they claim that the most common anomaly involving the coronary artery is the one of the circumflex branch, although such anomalies are not common in adults. It must be considered however, that this condition can be present at birth, being little symptomatic during childhood, and being found incidentally through the coronary arteriography or necropsy.…”
Section: Discussionsupporting
confidence: 67%
“…The retroaortic course is the most common and is seen in up to 0.9% of the population, particularly in cases in which the left Cx arises from either the right sinus of Valsalva or the RCA. [3] While the retroaortic or prepulmonic course is considered to be "benign" or "nonmalignant", Samarendra et al [5] suggested that when the Cx arises from the contralateral sinus with a retroaortic course, it may result in a predisposition toward selective coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Retroaortic course of a solitary coronary artery, although much rarer, may be of clinical significance, as it has been suggested that this pattern potentiates to premature atherosclerotic disease (Samarendra et al, 2001;Angelini, 2007). Anomalous arteries taking a prepulmonary course run anteriorly across the free-standing subpulmonary infundibulum from their anomalous sinusal …”
Section: Anomalous Sinus Originmentioning
confidence: 99%